Earlobe hypertrophy correction - Manuel Mário Gomes Faial; Dushane Dominick Pinnock (Revista Brasileira de Cirurgia Plástica, 2017)
INTRODUCTION: The ear is a structure of the face with important aesthetic value. The dimensions of the ear and the appearance of its anatomical components change with age, disease and cultural practices which can result in an aesthetically unpleasant form over time. The earlobe is an important anatomical part of the ear and is considerably influenced by the factors above. It is made of fatty tissue and skin and can undergo changes in its proportion and flaccidity, which may be improved by surgical procedures to make it more aesthetically pleasing, providing a more proportional or younger appearance. This article reports the case of a 30-year-old patient who considered his earlobes disproportionate in relation to the rest of his ears and underwent surgery to have them reduced. METHODS: A simple and fast recovery surgical procedure was carried out delineating and resecting a part of each of the patient's earlobes. RESULTS: The results proved to be satisfactory as the patient had more proportional earlobes in relation to the rest of his ears achieving aesthetic improvement. CONCLUSION: The technique described in this article to reduce hypertrophied earlobes proved to be efficient.